Changes in Digital Communication During the COVID-19 Global Pandemic: Implications for Digital Inequality and Future Research. (September 2020) - Nguyen, Minh Hao; Gruber, Jonathan; Fuchs, Jaelle; Marler, Will; Hunsaker, Amanda; Hargittai, Eszter
Governments and public health institutions across the globe have set social distancing and stay-at-home guidelines to battle the COVID-19 pandemic. With reduced opportunities to spend time together in person come new challenges to remain socially connected. This essay addresses how the pandemic has changed people's use of digital communication methods, and how inequalities in the use of these methods may arise. We draw on data collected from 1, 374 American adults between 4 and 8 April 2020, about two weeks after lockdown measures were introduced in various parts of the United States. We first address whether people changed their digital media use to reach out to friends and family, looking into voice calls, video calls, text messaging, social media, and online games. Then, we show how age, gender, living alone, concerns about Internet access, and Internet skills relate to changes in social contact during the pandemic. We discuss how the use of digital media for social connection during a global public health crisis may be unequally distributed among citizens and may continue to shape inequalities even after the pandemic is over. Such insights are important considering the possible impact of the COVID-19 pandemic on people's social wellbeing. We also discuss how changes in digital media use might outlast the pandemic, and what this means for future communication and media research.